MOVEMENT ANALYSIS OF KARACHI STOCK EXCHANGE (1993 - 2012) - Alam, Sadaf; Muzafar, Dawood (European Scientific Journal, ESJ, 2014)
The variation in the stock market prices is a significant indicator of the economy. The intention of this study was to examine the movement analysis of the Karachi stock market. For this, the yearly data of money supply, interest rate (discount rate), inflation rate, exchange rate, gold prices, industrial production (GDP) as independent variables and stock market returns (KSE-100 index) as dependent variable over the period of 1993 – 2012 is collected. Descriptive statistics, Regression analysis, Augmented Dickey Fuller (ADF) unit root test and Johansen co integration models are used to test the movement of macroeconomic factors affecting on stock market return. The empirical outcome shows that money supply, rate of inflation, gold prices, industrial production have positive association with stock market return while interest rate and exchange rate correlate negatively with stock market. Finding reveals that money supply is the largest positive determinant of the stock market return while interest rate is largest negative determinant of movement in Karachi stock market. These results further signified that gold prices used as diversification tool to hedge against inflation in slump economy, contractionary monetary policy generally depress equity return in short-term as well as long-term and furthermore increasing in economic productivity promotes stock market development.